Melanoma mortality following skin cancer screening in Germany. Issue 9 (15th September 2015) - Boniol, Mathieu; Autier, Philippe; Gandini, Sara
Abstract : Objectives: In 2003, a skin cancer screening campaign based on total body skin examination was launched in the federal state of Schleswig-Holstein, Germany. 20% of adults aged 20 and over were screened. In 2008, a 48% decline in melanoma mortality was reported. In the same year, skin screening was extended to the rest of Germany. We evaluated whether melanoma mortality trends decreased in Germany as compared with surrounding countries where skin screening is uncommon. We also evaluated whether the initial decreasing mortality trend observed in Schleswig-Holstein was maintained with a longer follow-up. Setting and participants: Regional and national melanoma mortality data from 1995 to 2013 were extracted from the GEKID database and the Federal Statistical Office. Mortality data for Germany and surrounding countries from 1980 to 2012 were extracted from the WHO mortality database. Primary and secondary outcome measures: Age-adjusted (European Standard Population) mortality rates were computed and joinpoint analysis performed for Schleswig-Holstein, Germany and surrounding countries. Results: In Schleswig-Holstein, melanoma mortality rates declined by 48% from 2003 to 2008, and from 2009 to 2013 returned to levels observed before screening initiation. During the 5 years of the national programme (2008–2012), melanoma mortality rates increased by 2.6% (95% CI −0.1 to 5.2) in men and 0.02% (95% CI −1.8 to 1.8) in women. No inflexion point in trends was identified after 2008 that could have suggested a decreasing melanoma mortality. Trends of cutaneous melanoma mortality in Germany from 1980 to 2012 did not differ from those observed in surrounding countries. Conclusions: The transient decrease mortality in Schleswig-Holstein followed by return to pre-screening levels could reflect a temporal modification in the reporting of death causes. An in-depth evaluation of the screening programme is required.